Tradition of Besan Bali Marriage in the Muslim Community of Banjarnegara - Hariyanto Hariyanto (IBDA` : Jurnal Kajian Islam dan Budaya, 2022)
This article examines how the Besan Bali marriage tradition in the Muslim community of Banjarnegara and an overview of Islamic law. This type of research is a field research, using qualitative methods with a qualitative descriptive approach. The interview method was used to obtain direct data from the informants. The types of data are primary and secondary data. The results of this study show that the Besan Bali marriage tradition is a tradition of prohibition in marriages that occur between two brothers (besan) that someone who wants to hold a marriage is hindered if the-bride-to-be comes from the Besan family where previously her brother was married to her groom-to-be’s family and vice versa. If it is reviewed based on Islamic law, the prohibition of Besan Bali marriage is actually not in accordance with Islamic teachings, because the reason for the prohibition of Besan Bali marriage is not in accordance with Islamic teachings.